P-137 ICM and TE quality significantly impact the live birth in euploid frozen blastocyst transfer cycles. (30th June 2022) - Liñán Tegedor, A; Elkhatib, I; Arnanz, A; Bayram, A; Abdala, A; Ruiz, F; Shanker, U; Akram, A; Melado, L; Patel, R; Lawrenz, B; Fatemi, H.M
Abstract: Study question: Is the live birth rate (LBR) in euploid frozen blastocyst transfer (FET) affected by the quality of ICM (Inner cell mass) and TE (Trophectoderm)? Summary answer: ICM and TE significantly impacts the LBR with a decline of LB from 57.3% (ICM-A) to 48.5% (ICM-B) to 22.1% (ICM-C) (p < 0.001) What is known already: The morphological blastocyst grading system proposed by Gardner-Schoolcraft remains the most accepted system to identify blastocysts with higher implantation potential. It relies on morphological features within the blastocyst, including ICM and TE. Several studies tried to identify the individual contribution of each. However, the conclusions remain contradictory and no clear consensus has yet been achieved. Due to heterogeneity of parameters evaluated between different publications, where embryos with unknown ploidy status were transferred in conjunction with a variability of stimulation protocols and in the number of transferred embryos, the real effect of the ICM and TE is difficult to infer. Study design, size, duration: This two-center retrospective observational study includes a total of 977 euploid single FET cycles between March 2017 and March 2020 at ART Fertility Clinics Muscat, Oman and Abu Dhabi, UAE. Participants/materials, setting, methods: Trophectoderm biopsies were analyzed with Next Generation Sequencing (NGS). All blastocysts available on D5 or D6 with a quality ≥ BL3CC were subjected to TE biopsy for PGT-A analysis and LBR was recorded. Vitrification/warming of blastocysts was performed using Cryotop method (Kitazato). Bivariate and multivariate analysis were performed between LB outcomes and ICM and TE grade while controlling for confounding factors. Main results and the role of chance: A total of 977 single FET cycles were analyzed: 651 in hormone replacement therapy (HRT) and 326 in natural cycle regimen (NC) resulting in a 46.88% LBR. The mean patients' age was 33.80 years with a mean Body Mass Index (BMI) of 26.80 kg/m 2 . Though all qualities of ICM and TE were associated with LB, blastocyst ICM-A LBR was statistically significantly higher (57.3%) than ICM-B (48.4%) and ICM-C (22.1%) (p < 0.001). Similarly, blastocyst TE-A LBR was statistically significantly higher (59.2%) than TE- B (48.6%) and TE- C (30.3%) (p < 0.001). Miscarriage rate was similar in all groups. The grade of ICM and TE were significantly associated with Anti-Mullerian-Hormone (AMH) and day of blastocyst biopsy. Mean AMH (ng/ml) was higher in ICM groups (A: 3.78, B: 3.24, p < 0.001) and TE group (A: 3.63, B: 3.38, p < 0.05) compared to lower grade (ICM-C: 2.86, TE-C: 2.82). In multivariate analysis, endometrial preparation for FET, BMI and AMH were the parameters influencing LBR: OR:1.45, [CI:1.07-1.96], p < 0.015) for NC; OR 0.96 [CI:0.93-0.99], p = 0.004 for BMI; OR 0.95 [CI:0.90-1.00], p = 0.033 for AMH; Both, ICM-C and TE-C, resulted in a significantly lower chance of LB [ICM: OR 0.32, CI:0.17-0.61, p < 0.001; TE: OR 0.44, CI:0.27-0.73, p = 0.002), compared to grade A. Limitations, reasons for caution: The retrospective nature of the study and inter-observer variability in blastocyst scoring is a limitation. The physician/embryologist performing the embryo transfer could not been standardized due to the multicenter design. Randomized controlled studies are needed to determine whether ICM or TE should be prioritized in the selection of the blastocyst. Wider implications of the findings: The ICM and TE scoring in FET may influence the LBR and should be considered as an important factor for the success of embryo transfer cycles. Whether these results can be extrapolated to fresh embryo transfer and to blastocysts with unknown ploidy status, needs further investigation. Trial registration number: not applicable